SINTESIS SURFAKTAN METIL ESTER SULFONAT (MES) DARI METIL LAURAT - Nur Iman; Abdul Rahman Razak; Nurhaeni Nurhaeni (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
Synthesis of surfactant methyl ester sulfonate (MES) of methyl laurate has been done. This study aims to determine the best mole ratio between the methyl esters of lauric acid with sulfonated agent NaHSO3 in sulfonated methyl laurate. Mole variation used in this study are 1:1; 1:1,2; 1:1,4 and 1;1,6 (v/w). Best value MES emulsion stability, acid value and the surface tension is 94,5 minutes,1.3 ml KOH/ g sample, 39.3 dyne/cm in 1:4 ratio produces. MES synthesis produced by sulfonate group shown in the FTIR spectra in the wave number around 1366.52 to 1015.30 cm. Keywords : Surfactant Methyl Ester Sulfonate, Methyl Laurate.